Multistimuli-responsive interconvertible low-molecular weight metallohydrogels and the in situ entrapment of CdS quantum dots therein - Bera, Saibal; Chakraborty, Amit; Karak, Suvendu; Halder, Arjun; Chatterjee, Soumyajyoti; Saha, Subhadeep; Banerjee, Rahul (Chemistry of Materials, 2018)
Two low molecular weight metallohydrogels (ZALA and CALA) have been synthesized from an amino-acid based ligand precursor (LA) and two different metal salts [zinc acetate dihydrate (ZA) and cadmium acetate dihydrate (CA), respectively. These two hydrogels show a unique chemically stimulated interconversion to each other via a reversible gel-sol gel pathway. This programmable gel-sol reversible system satisfies logic operations of a basic Boolean logic (INHIBIT) gate. Also, these hydrogels can be degraded into different MOF phases at room temperature spontaneously or in the presence of chloride and bromide salts (NaCl and NaBr.). CdS quantum dots can be grown inside the CALA gel matrix (CdS@CALA) in the presence of small amount of Na2S. This CdS doped gel exhibits time dependent tunable emission (white to yellow to orange) as a consequence of a slow agglomeration process of the entrapped quantum dots inside the gel matrix. This luminescence property also reflects the corresponding gel derived MOFs (obtained either by self-degradation of CdS@CALA or via anion induction) as well. This, to the best of our knowledge, is probably the simplest way to make a CdS quantum dot based composite material where CdS is entrapped within the gel and the gel-derived MOF matrix.